A retrospective study of ABI and TBI during the healing of ulcer among diabetic patients. Issue 1 (January 2019) - Zubair, Mohammad; Al Amri, Marai; Ahmad, Jamal
Abstract: Objective: To assess the role of ABI and TBI in the detection of ulcer wounds among diabetic patients. Methods: A retrospective approach is used to enroll 192 diabetic patients to detect their ulcer wounds using ABI and TBI index. HbA1c and lipid profile were other important variables in determining the efficacy of screening test. Frequency analysis and Pearson Correlation were used to analyze the data through SPSS. Findings: The results have shown that 57.1% male and 42.9% female were treated in <0.60 ABI group; 67.4% male and 32.6% female were treated in 0.60–0.90 ABI group; 65.9% male and 34.1% female were treated in 0.90–1.30 ABI group; and 63.8% male and 36.2% female were treated in >1.30 ABI group. The correlation showed insignificant association between ABI and ulcer outcomes, but significant association between TBI and ulcer outcomes at 5% level of significance. Conclusion: The study concluded that ABI should be based on standardized normal values to be used as an effective biomarker in screening diabetic foot ulcer patients.